2012
DOI: 10.1038/bmt.2012.175
|View full text |Cite
|
Sign up to set email alerts
|

A phase II study of sirolimus, tacrolimus and rabbit anti-thymocyte globulin as GVHD prophylaxis after unrelated-donor PBSC transplant

Abstract: We report on a prospective phase II trial of 32 patients who underwent unrelated donor hematopoietic cell transplantation, with a tacrolimus, sirolimus and rabbit anti-thymoctye globulin GVHD prophylactic regimen. The primary study endpoint was incidence of grades II-IV acute GVHD, with 80% power to detect a 30% decrease compared to institutional historical controls. Median age at transplant was 60 (19-71). Twenty-three patients (72%) received reduced-intensity conditioning, while the remainder received full-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 22 publications
(23 reference statements)
2
22
1
Order By: Relevance
“…Unlike previously published evidence, 17,18,21,22 the combination of TAC and SIR did not appear to pose a higher risk of TA-TMA than with TAC/MTX±ATG. These results are in agreement with a retrospective study in which the incidence of TA-TMA in patients who were given TAC/SIR ± ATG was not significantly different from that in patients who received MTX with TAC or CYA (10.2% vs 4.3%), 23 or with those of a recently randomized phase II trial comparing TAC/SIR with TAC/MTX, 24 although the high incidence of TA-TMA reported in this latter trial (24.3% with TAC/SIR and 18.9% with TAC/MTX) should be noted.…”
Section: Baseline Characteristics Of Patientscontrasting
confidence: 54%
See 2 more Smart Citations
“…Unlike previously published evidence, 17,18,21,22 the combination of TAC and SIR did not appear to pose a higher risk of TA-TMA than with TAC/MTX±ATG. These results are in agreement with a retrospective study in which the incidence of TA-TMA in patients who were given TAC/SIR ± ATG was not significantly different from that in patients who received MTX with TAC or CYA (10.2% vs 4.3%), 23 or with those of a recently randomized phase II trial comparing TAC/SIR with TAC/MTX, 24 although the high incidence of TA-TMA reported in this latter trial (24.3% with TAC/SIR and 18.9% with TAC/MTX) should be noted.…”
Section: Baseline Characteristics Of Patientscontrasting
confidence: 54%
“…1,3,5,8,[10][11][12][13][14] The use of TAC plus SIR as GVHD prophylaxis has been associated with an increased incidence of TA-TMA, which ranges from 10.8-55%, the latter in patients who received BU plus CY as part of their conditioning regimen. [17][18][19]21,22 In a recent phase II multicenter prospective trial conducted by our group, including some of the patients in this study, no differences were observed in the incidence of TA-TMA when TAC/SIR was compared with patients included in a prior prospective trial using CYA-mycophenolate (the overall incidences of TA-TMA were 10% and 6%, respectively). 25 In addition, very few studies 23,24 have evaluated the risk of TA-TMA among patients receiving the TAC/SIR combination in comparison with other TAC-based regimens.…”
Section: Baseline Characteristics Of Patientsmentioning
confidence: 93%
See 1 more Smart Citation
“…2-4 Several publications indicated that the risk of TA-TMA was substantially higher with the combination of TAC and sirolimus. [13][14][15] In our cohort, no higher risks with TAC and sirolimus combinations were observed compared with other TAC-containing regimens, in line with findings of Labrador et al 11 With regards to conditioning intensity, reports demonstrate controversial results. 2,5,[10][11][12] In this study, we detected an increased risk of TA-TMA, when MAC was applied.…”
Section: Discussionsupporting
confidence: 75%
“…1 Although the exact pathophysiology remains unclear, endothelial dysfunction with platelet activation and formation of platelet-rich thrombi in the microcirculation are regarded as key elements, leading to platelet consumption, mechanical damage to red blood cells and secondary organ damage. 2, 3 The role of predisposing risk factors has been addressed, 2,4-6 such as female gender, 7,8 older age, 9,10 lymphoid malignancy, 11 unrelated donor, 7,10 HLA mismatch, 9 conditioning and immunosuppressive regimens, 7,[10][11][12][13][14][15][16] infections, 3,9,11,17 acute GvHD (aGvHD) 7,[10][11][12]17,18 and ABO incompatibility. 19 Acquired idiopathic thrombotic thrombocytopenic purpura (TTP) also belongs to the family of thrombotic microangiopathies.…”
Section: Introductionmentioning
confidence: 99%